واقع أزمة سد النهضة وخيارات التسوية 2011-2021 - زبير, الصالح (جامعة الوادي.University eloued, 2021)
ترمي هذه الدراسة إلى إلقاء الضوء على واقع أزمة سد النهضة الإثيوبي في نهر النيل بين دولة المنبع إثيوبيا ودولتي المصب مصر والسودان مع عرض لتطورات الأزمة كذلك التطرق إلى القانون الدولي للأنهار و كذا الاتفاقيات التاريخية المنظمة لاستخدام مياه نهر النيل وما يقابلها من إشكاليات حول تقاسم هذه المياه، مرورا بالتدخلات الخارجية سواء كانت بصفة مباشرة أو غير مباشرة والتي ساعدت على تأجيج النزاع المائي وزيادة حدة الأزمة بين هاته الدول في منطقة القرن الإفريقي وانعكاساتها على الأمن القومي لمصر والسودان، كما تناولت الدراسة مفاوضات التي اعتمدت من اجل الخروج بالأزمة إلى بر الأمان والتوصل إلى اتفاق يرضي الأطراف الثلاثة، وفي الأخير تم التطرق إلى مستقبل أزمة سد النهضة ممثلة في ثلاثة سيناريوهات أولها خيار التعاون يليها خيار التحكيم الدولي ومن ثم الخيار العسكري .This study aims to shed light on the reality of the crisis of the Grand Ethiopian Renaissance Dam in the Nile River between the upstream country Ethiopia and the downstream countries Egypt and Sudan with a presentation of the developments of the crisis as well as addressing the international law of rivers, as well as the historical agreements regulating the use of the Nile water and the corresponding problems around sharing These waters, passing through external interventions, whether directly or indirectly, which helped fuel the water conflict and exacerbate the crisis between these countries in the Horn of Africa and its repercussions on the national security of Egypt and Sudan, The study also dealt with the negotiations that were adopted in order to get out of the crisis to safety and reach an agreement that satisfies the three parties, and in the end, the future of the Renaissance Dam crisis was addressed, represented in three scenarios, the first of which is the option of cooperation, followed by the option of international arbitration and then the military option.
ماستر سياسة عامة
Keywords: سد النهضة الاثيوبي; This study aims to shed light on the reality of the crisis of the Grand Ethiopian Renaissance Dam in the Nile River between the upstream country Ethiopia and the downstream countries Egypt and Sudan with a presentation of the developments of the crisis as well as addressing the international law of rivers, as well as the historical agreements regulating the use of the Nile water and the corresponding problems around sharing These waters, passing through external interventions, whether directly or indirectly, which helped fuel the water conflict and exacerbate the crisis between these countries in the Horn of Africa and its repercussions on the national security of Egypt and Sudan, The study also dealt with the negotiations that were adopted in order to get out of the crisis to safety and reach an agreement that satisfies the three parties, and in the end, the future of the Renaissance Dam crisis was addressed, represented in three scenarios, the first of which is the option of cooperation, followed by the option of international arbitration and then the military option.